PENGARUH KINERJA PERSONIL DI AIR SIDE TERHADAP ON TIME PERFORMANCE PENERBANGAN DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - I Made Andika Bramantha; Lusiana Dewi Kusumayati; Yuyun Suprapto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
I Gusti Ngurah Rai Bali International Airport is one of airports in Indonesia with heavy flight traffic. To always improve the convenience of the aviation service users and to keep them trusting the flight service, aviation airlines with airport personnel always make efforts to maintain flight on time performance. One of the personnel on duty on the air side is Operator Aviobridge which is the sub unit of Apron Movement Control where their performance will have significant impact to flight on time performance. Data collection method used in this research is using direct observation and questionnaire filling. Analysis method used in this research is quantitative descriptive which there is validity test, reliability test, and simple regression analysis. The result of this research shows that the effect of Operator Aviobridge personnel performance to flight on time performance is amounting to 83,4% whereas 16,6% be affected by other factors which is not researched.